Does economic growth and energy consumption drive environmental degradation in China's 31 provinces? New evidence from a spatial econometric perspective. Issue 42 (8th September 2019) - Zhang, Wen-Wen; Sharp, Basil; Xu, Shi-Chun
ABSTRACT: The panel data analysis points to economic and social factors contributing to NOx, PM2.5, PM10, SO2, and VOCs in China's 31 provinces. The spatial correlation analysis using Global and Local Moran's I values indicates the existence of a significant and positive spatial autocorrelation with respect to environment, economy and energy, and the high spatial correlation is evident in the eastern region, covering the northern part of Yangtze River Delta, Huaihai Economic Zone, and the lower reaches of the Yellow River Economic Belt. The empirical estimation is performed through spatial lag and spatial Durbin models. All emitted air pollutants in 31 provinces have significant spatial dependence and strong spillover effects. There is an inverted U-shaped relationship between emitted air pollutants (NOx, PM10, VOCs, and PM2.5 ) and per capita GDP, which follows the EKC hypothesis. The relationship between SO2 and per capita GDP does not follow the EKC hypothesis. There is a positive relationship between pollutant emissions and coal consumption, which is consistent with current studies for various countries like Canada, Denmark, UK and US and regions like New York State. However, the effects of science and technology investment on air pollutants are mostly positive, which is not as policy expected.